Phenomenon of Demikhov. At N.V. Sklifosovsky Institute (1960–1986). V.P. Demikhov and world transplantology in 1968-1969 - S. P. Glyantsev (Трансплантология (Москва), 2021)
The article has reviewed the advances of Soviet and world Transplantology in the field of heart and other organ transplantation achieved by the end of the 1960s. It is shown that there were several groups of doctors and scientists who worked in the USSR dealing with the problem of experimental organ transplantation and trying to bring this experience into clinic. The group of surgeons and urologists (B.V. Petrovsky, Y.M. Lopukhin, etc.) from the Research Institute of Clinical and Experimental Surgery and the 2nd MOLGMI named after N.I. Pirogov, which had the greatest administrative resources and technical capabilities, was successfully implementing kidney transplantation into clinic. The staff of the Faculty Surgery Department (V.S. Savelyev and others) of the 2nd MOLGMI named after N.I. Pirogov developed experimental approaches to heart and liver transplantation. Surgeons from the Tuberculosis Research Institute (N.I. Gerasimenko and others) were dealing with in lung auto- and homotransplats in experiment. All those studies were conducted in close contact with the Department of Operative Surgery and Topographic Anatomy of the 2nd MOLGMI named after N.I. Pirogov (G.E. Ostroverkhov) and the Research Laboratory for Organ Transplantation established at that Department (Y.M. Lopukhin). The leading position in heart transplantation in the country belonged to the Vishnevsky Institute of Surgery (A.A. Vishnevsky, etc.). Surgeons of the MMA named after S.M. Kirov (I.S. Kolesnikov, etc.) rendered a great assistance to the Institute. Apart from these institutions, the Organ Transplantation Laboratory (headed by V.P. Demikhov) worked at N.V. Sklifosovsky Research Institute for Emergency Medicine; it had gained a huge experimental experience, but had very modest opportunities to purchase equipment and pharmaceuticals, to conduct laboratory and morphological studies, having practically no prospects for introducing the results of its research into clinic. Meanwhile, the world clinical Transplantation continued to develop successfully, which was reflected in the materials of the 2nd International Symposium on Heart Transplantation held in 1969 in Montreal (Canada).